On the Origins of Entrepreneurship: Evidence from Sibling Correlations - Matthew J. Lindquist; Joeri Sol; Mirjam C. van Praag; Theodor Vladasel (Institute for the Study of Labor (IZA), 2016)
Promoting entrepreneurship has become an increasingly important part of the policy agenda in many countries. The success of such policies, however, rests in part on the assumption that entrepreneurship outcomes are not fully determined at a young age by factors that are unrelated to current policy. We test this assumption and assess the importance of family background and neighborhood effects as determinants of entrepreneurship, by estimating sibling correlations in entrepreneurship. We find that between 20 and 50 percent of the variance in different entrepreneurial outcomes is explained by factors that siblings share (i.e., family background and neighborhood effects). The average is 28 percent. Hence, entrepreneurship is far less than fully determined at a young age. Our estimates increase only a little when allowing for differential treatment within families by gender and birth order. We then investigate a comprehensive set of mechanisms that explain sibling similarities. Parental entrepreneurship plays a large role in explaining sibling similarities, as do shared genes. We show that neighborhood effects matter, but are rather small, particularly when compared with the overall importance of family factors. Sibling peer effects, and parental income and education matter even less.
Keywords: D13; J62; L26; 330; entrepreneurship; family background; intergenerational persistence; neighborhood effects; occupational choice; sibling correlations